The Base of the Iceberg Informal Learning and Its Impact on Formal and Non-formal Learning - Rogers, Alan (Study guides in Adult Education, 2014)
Alan Rogers looks at learning (formal, nonformal and informal) and examines the hidden world of informal (unconscious, unplanned) learning. He points out the importance of informal learning for creating tacit attitudes and values, knowledge and skills which influence (conscious, planned) learning - formal and non-formal. Moreover, he explores the implications of informal learning for educational planners and teachers in the context of lifelong learning. While mainly aimed at adult educators, the book's arguments apply also to schooling and higher education, in both industrialised societies and developing countries where large numbers of children and adults are not and have not been in school and so rely on informal learning to manage change.